Dynamic comparison of a railway catenary section upgrade by field measurement assessments. (2017) - Nåvik, Petter; Rønnquist, Anders
Abstract: The pantograph-catenary interaction is crucial for running trains on electrical railway lines. The coupled dynamic problem of an in space stationary system, the catenary system, and a system in motion, the pantograph, is dependent on the behaviour of both combined as well as individually. Different catenary systems exhibit different behaviour. This paper evaluates a catenary system upgrade by dynamic assessment. Existing railway catenary sections are upgraded or replaced due to wear, but also due to an aim for improved running quality or increased speed on the rail line. Field measurements were conducted on an old catenary section. This section was then upgraded, and some months later measurements were conducted on the new catenary section. Thus, field measurements were sampled at the same location twice. Since the measurements were sampled only months apart and that all measurements are recording behaviour under regular train operation, the loading is assumed to be identical. Dynamic assessment of both sections has been done using power spectral densities and histograms. Important differences and similarities in their response can be seen. This study further increases the knowledge regarding the dynamic behaviour of railway catenary sections when evaluating the impact of the upgrades.